2020
DOI: 10.21037/tau-20-689
|View full text |Cite
|
Sign up to set email alerts
|

Baseline patient reported outcomes data shows high prevalence of overactive bladder, sexual dysfunction, depression and anxiety in Canadian men with newly diagnosed localized prostate cancer

Abstract: Background: Research on prostate cancer survivorship patients has largely been on oncological outcome, incontinence and erectile dysfunction, with less data on the relationship between prostate cancer, bladder function and mental health. This study aims to elucidate the prevalence of lower urinary tract symptoms (LUTS), overactive bladder (OAB), sexual dysfunction, depression and anxiety in Canadian men with newly diagnosed localised prostate cancer.Methods: This is a single-centre prospective cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Although less frequently studied, other LUTS are not uncommon after RP [ 5 ]. Unfortunately, the high preoperative incidence of LUTS further complicates research on the impact of surgery on lower urinary tract (LUT) function afterwards [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although less frequently studied, other LUTS are not uncommon after RP [ 5 ]. Unfortunately, the high preoperative incidence of LUTS further complicates research on the impact of surgery on lower urinary tract (LUT) function afterwards [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 Research has previously shown the rate of overactive bladder (OAB) to be 55.8% in men with newly diagnosed prostate cancer. 6 Men with LUTS due to benign prostate hyperplasia (BPH) are more likely to seek medical attention, undergo investigations, and be diagnosed with prostate cancer. 7,8 It is important to address both LUTS and prostate cancer in wholistic patient management.…”
Section: Introductionmentioning
confidence: 99%
“…26 We observed lower urinary and bowel functional domain scores in men reporting higher problems with feeling depressed and lack of energy. While we are uncertain of causality, it is known that poor urinary symptoms following treatment are associated with poorer patient reported outcomes in terms of overall quality of life, 27,28 depression, 29 regret over treatment decisions, 30 sexual functioning, 31,32 34 Further, the use of a single question within a larger tool has been shown to be clinically useful in patients with cancer. 35 A single question of the Edmonton Symptom Assessment System (where the patient answers on a one to 10 ordinal scale from not depressed to worst possible depression) demonstrated acceptable performance in screening of depression detected by the HADS 36 or the depression subscale of the PHQ-9.…”
Section: Discussionmentioning
confidence: 99%
“…We observed lower urinary and bowel functional domain scores in men reporting higher problems with feeling depressed and lack of energy. While we are uncertain of causality, it is known that poor urinary symptoms following treatment are associated with poorer patient reported outcomes in terms of overall quality of life, 27,28 depression, 29 regret over treatment decisions, 30 sexual functioning, 31,32 and relationship quality 33 …”
Section: Discussionmentioning
confidence: 99%